Medical and Surgical Treatment in Pediatric Orbital Myositis Associated with Coxsackie Virus - Pedro Gil; João Gil; Catarina Paiva; Guilherme Castela; Rui Castela (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of orbital myositis associated with Coxsackie virus and its medical and surgical approach. Methods. Complete ophthalmological examination and imaging and analytical investigation were performed. Results. A 6-year-old male presented with subacute painless binocular horizontal diplopia. Examination revealed bilateral best-corrected visual acuity (BCVA) of 20/20 and right eye 45-prism-dioptre (PD) esotropia in near and distance fixations, with no motility restrictions. Serologic screening was positive for Coxsackie virus acute infection and computerized tomography (CT) suggested right eye medial rectus orbital myositis. An oral corticosteroid 1.0 mg/kg/day regimen was started. A new CT after two months showed symmetrical lesions in both medial rectus muscles. Corticosteroids were increased to 1.5 mg/kg/day. After imagiological resolution on the 4th month, alternating 45 PD esotropia persisted. Bilateral 7 mm medial rectus recession was performed after 1 year without spontaneous recovery. At 1-year follow-up, the patient is orthophoric with 200′′ stereopsis and bilateral 20/20 BCVA. Conclusions. To our knowledge, this is the first reported case of orbital myositis associated with Coxsackie virus. This is also the first reported case of isolated strabismus surgery after orbital myositis in pediatric age, highlighting the favourable aesthetic and functional outcomes even in cases of late ocular motility disorders.